Assessment of Oral Health Related Knowledge, Attitude, and Self-Reported Practices of Families Residing in Peshawar, Pakistan - Qadir, Syed Abdul; Shahzad, Muhammad; Yousafzai, Yasar Mehmood (ADVANCES IN BASIC MEDICAL SCIENCES, 2019)
Introduction: Oral health is an integral component of one’s general health and overall wellbeing. Oral diseases are a common occurrence across the globe and require community based preventive improve oral health at population level. Knowledge, attitude and practice (KAP) survey is an important pre-requisite before launching community based oral health promotion programs. Objectives: The aim of the present study was to assess oral health knowledge, attitude and practice of families residing in Peshawar, Pakistan. Methodology: It was a cross sectional study, conducted on 200 participants residing in a suburban locality of District Peshawar. Data was collected using a modified structured questionnaire and analyzed using SPSS software. Results: Oral health related knowledge of the participants about specific dental problem was not satisfactory. Regular dental checkup is uncommon and dental pain is the main reason for visiting dentist (65%). Dental fear and anxiety is also common (61%). About 98% of participants reported to brush their teeth and tooth paste and brush is the most common tool for cleansing teeth (73%). Conclusion: Oral health knowledge about dental disease and oral care seeking behavior of the population is not satisfactory thereby requiring awareness campaigns to improve oral hygiene and health.